2015
DOI: 10.1002/acr.22587
|View full text |Cite
|
Sign up to set email alerts
|

Association of Objectively Measured Physical Activity and Metabolic Syndrome Among US Adults With Osteoarthritis

Abstract: Objective To investigate the association between objectively-measured physical activity and metabolic syndrome among adults with osteoarthritis (OA). Methods Using cross-sectional data from 2003–2006 NHANES, we identified 566 adults with OA with available accelerometer data assessed using Actigraph AM-7164 and measurements necessary to determine metabolic syndrome by Adult Treatment Panel III. Analysis of variance was conducted to examine the association between continuous variables in each activity level an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…However, results from a recent population‐based cohort study showed that hip OA or knee OA is a strong contributor to walking difficulty , and only a small‐to‐moderate proportion of patients with hip OA or knee OA meet the guidelines for physical activity . Many patients with OA spend a considerable amount of time being sedentary, leading to more impairment in physical function, reduced walking speed , and poorer cardiometabolic health compared with their peers who had a less sedentary lifestyle. Therefore, assessment of cardiorespiratory fitness should be prioritized in clinical practice , and improved cardiorespiratory fitness should be a treatment goal, in order to prevent cardiovascular co‐morbidity in OA.…”
Section: Discussionmentioning
confidence: 99%
“…However, results from a recent population‐based cohort study showed that hip OA or knee OA is a strong contributor to walking difficulty , and only a small‐to‐moderate proportion of patients with hip OA or knee OA meet the guidelines for physical activity . Many patients with OA spend a considerable amount of time being sedentary, leading to more impairment in physical function, reduced walking speed , and poorer cardiometabolic health compared with their peers who had a less sedentary lifestyle. Therefore, assessment of cardiorespiratory fitness should be prioritized in clinical practice , and improved cardiorespiratory fitness should be a treatment goal, in order to prevent cardiovascular co‐morbidity in OA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies about the effects of physical activity on the metabolic syndrome in bipolar patients showed uncertain results. Similarly to other physical and mental conditions (Kahl et al, 2015;Liu et al, 2015;Park and Larson, 2014), physical activity should improve anthropometric measures and impact positively on metabolic syndrome. Possibly, an explanation for the few available studies may be the difficulty in recruiting and the adherence to physical exercise in bipolar population with frequent severe behavioral symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, dyslipidemia, impaired fasting glucose, and hypertension have been hypothesized to contribute to OA incidence and progression 8,9 and, in turn, OA has been hypothesized as an independent 'metabolic' risk factor for CVD. A number of cross-sectional studies have demonstrated a positive association between the presence of OA, variably defined, and both metabolic syndrome and CVD 4,5,10 ; these relationships appear stronger for hand and knee OA than for hip OA. More recently, it has also been shown in longitudinal studies that people with symptomatic hip, knee, and possibly hand OA are at increased risk for CVD 11e13 relative to the age-and sex-matched general population or to non-OA controls.…”
Section: Introductionmentioning
confidence: 99%